Structural, Compositional, and Plasmonic Characteristics of Ti–Zr Ternary Nitride Thin Films Tuned by the Nitrogen Flow Ratio in Magnetron Sputtering - Lianlian Chen; Yujing Ran; Zhaotan Jiang; Yinglan Li; Zhi Wang (Nanomaterials, 2020)
Ternary nitride gives high diversity and tunability of the plasmonic materials. In this work, highly crystallized ternary (Ti, Zr)N <semantics> x </semantics> films were prepared by magnetron co-sputtering with different nitrogen gas flow ratio <semantics> R n </semantics> . The structural and plasmonic properties of the films tuned by <semantics> R n </semantics> were investigated. All the films are solid solutions of TiN <semantics> x </semantics> and ZrN <semantics> x </semantics> with a rocksalt structure and (111) preferred orientation. The films are nitrogen-overstoichiometric and the main defects are cation vacancies. Increased <semantics> R n </semantics> reduces the zirconium content, and therefore leads to the reduction of lattice constant and enhancement of the crystallinity. As <semantics> R n </semantics> increases, the screened plasma frequency decreases for the reduction of free electron density. The maximum of the energy loss spectra of (Ti, Zr)N <semantics> x </semantics> films shifts to long-wavelength with <semantics> R n </semantics> increasing. The calculated electronic structure shows that increased nitrogen content enhances the electronic density of states of nitrogen and reduces that of metal, and therefore elevates the energy level at which interband transition is exited. The results show that (Ti, Zr)N <semantics> x </semantics> films give a relatively high plasmonic quality in the visible and near-infrared region, and the film properties can be significantly tuned by the nitrogen content.